Keutamaan Menikahi Gadis dalam Persfektif Islam: Studi Takhrij dan Syarah Hadis - Lutfi Muhammad Hamdani; Ahmad Tauviqillah (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about marrying girls. This research uses a qualitative approach by applying an analytical descriptive method. The formal object of this research is the science of hadith, while the material object is the hadith about marrying girls in Ibn Majah's narration No. 1850. The results and discussion of this study indicate that the status of the hadith is of saheeh quality that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the Hadith narrated by Ibn Majah No. 1850 is relevant to the development of the field of akhwal as-Syahsiyyah.